Effect of Crack Angle and Length on Mechanical and Ultrasonic Properties for the Single Cracked Sandstone Under Triaxial Stress Loading-Unloading - Hu, Huarui; Xia, Binwei; Luo, Yafei; Gao, Yugang (Frontiers in Earth Science, 2022)
The disturbance due to coal mining causes the surrounding rock to undergo a complex process of stress changes during which the axial pressure and the confining pressure usually change accordingly at the same time. Existing studies generally investigated this process from a static perspective, which was not rigorous. The mechanical characterization of rock is very important to understand the failure of rock mass and the safety of mining during mining disturbance. Based on theoretical analysis, we conducted axial loading and radial unloading tests on the cracked sandstone, which was combined with the ultrasonic testing technology to examine its failure rules and to characterize and analyze its failure process using longitudinal wave velocity. The results demonstrated that crack length and angle had a significant impact on the strength and mechanical properties of sandstone, and the former had a greater impact on the strength of sandstone than the latter. As the crack length increased, the strength, elastic modulus, and deformation modulus of sandstone decreased, and the strength of sandstone increased as the crack angle increased. Elastic and deformation moduli first decreased and then increased. Furthermore, Poisson’s ratio increased slowly, then decreased slowly, and finally increased rapidly as the lateral pressure coefficient diminished, and Poisson’s ratio was more sensitive to changes in the angle. In this study, the change of longitudinal wave velocity reflected the whole process of sandstone failure. When the wave velocity was stable, the rock was at the yield limit point. Moreover, when the wave velocity was unstable, the sandstone was in a progressive failure period, and as a result, the wave velocity decreased and the sandstone cracked.